Safety of a thermal vessel sealer on main pulmonary vessels - (:unkn) unknown (ELSEVIER SCIENCE BV, 2007)
Objective: LigaSure (Valleylab, Tyco Healthcare, Boulder, CO)is a novel instrument with widespread use in various surgical disciplines for vessel seating. It uses heat energy to denature collagen and elastin and achieve vessel seating. We investigated the safety of LigaSure in pulmonary arteries (PA) and veins (PV). Methods: Twelve sheep were anesthetized and endotracheally intubated. Six underwent right lower lobectomy (Group 1) and six right upper lobectomy (Group 2). All of the vessels in both groups were divided with LigaSure. Diameters of vessels were measured. Intraoperatively, pulmonary artery pressures (PAP) were monitored in Group 1. Following vascular division, ephedrine was injected to increase PAP in Group 1. In Group 2, animals were followed and euthanized at 7 days. Both immediate and 7 day samples were obtained from divided vessel stumps. Conventional histology was done. Statistical analysis was performed using t-test and Fisher's exact test. Results: Mean diameter of PAs (n = 9) divided in Group 1 was 8.3 mm (3-11) and of PVs (n = 8) was 10.4 mm (4-15). Mean PAP increased from 18 (27/9) to 27 (45/18) mmHg after ephedrine injection. Dehiscence rate was 2/6 in PAs and 3/6 in PVs larger than 9 mm in diameter. Mean diameter of PAs (n = 8) divided in Group 2 was 5.7 mm (3-7) and of PVs (n = 9) was 4.6 mm (4-6). No early or late (7 days) vascular disruption was seen in Group 2. Bleeding incidence was significantly different between groups (Fisher's exact test p = 0.015). Overall no dehiscence was observed in vessels less than 7 mm in diameter. Histology of intraoperative samples showed thermal injury and necrosis. Seven day samples showed short segment necrosis limited to the vessel watt, fibrosis, thrombus formation without inflammation, and minimal granulation tissue. Conclusions: LigaSure achieves perfect seating in pulmonary vessels less than 7 mm in diameter in sheep intra- and postoperatively even following a pressure challenge. It can safety be used in segmental branches of PAs and PVs during open or thoracoscopic surgery. (c) 2007 European Association for Cardio-Thoracic Surgery. Published by Elsevier B.V. All rights reserved.
Keywords: pulmonary artery; pulmonary vein; LigaSure; vascular division; STAPLELESS THORACOSCOPIC SURGERY; RANDOMIZED CLINICAL-TRIAL; LAPAROSCOPIC SPLENECTOMY; LIGASURE SYSTEM; SUTURELESS; RESECTION; LIGATION; DEVICE; SHEARS